2021
DOI: 10.21037/qims-20-280
|View full text |Cite
|
Sign up to set email alerts
|

Early-phase vascular involvement is associated with acute pancreatitis severity: a magnetic resonance imaging study

Abstract: Background: Although a number of studies have reported on the vascular abnormalities detected by magnetic resonance imaging (MRI) in patients with late-phase acute pancreatitis (AP), few have studied those occurring in the early phase of the disease. The aim of this research was to investigate the MRI findings of early vascular abnormalities in AP and to analyze the correlation of the prevalence of vascular involvement with the severity of AP based on the MR severity index (MRSI) and Acute Physiology and Chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Many studies have explored different aspects of AP using medical imaging. Jiang et al (12) reported that patients with early-phase AP frequently had vascular anomalies on magnetic resonance imaging (MRI), such as splenic vein phlebitis and splenic artery arteritis, which may serve as additional markers for pancreatitis severity. According to Peng et al (13), pleural effusion and pulmonary consolidation are associated with AP severity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have explored different aspects of AP using medical imaging. Jiang et al (12) reported that patients with early-phase AP frequently had vascular anomalies on magnetic resonance imaging (MRI), such as splenic vein phlebitis and splenic artery arteritis, which may serve as additional markers for pancreatitis severity. According to Peng et al (13), pleural effusion and pulmonary consolidation are associated with AP severity.…”
Section: Discussionmentioning
confidence: 99%
“…However, Zhou et al ( 32 ) demonstrated that extrapancreatic inflammation on CT scores have weak positive correlations with the APACHE II score. In addition, Peng et al ( 44 ) reported that the pleural effusion volume was correlated with the APACHE II score, and Jiang et al ( 45 ) found a significant correlation between the incidence of vascular involvement and AP severity on the basis of APACHE II score. In our study, the MCTSI score had a positive correlation with the RAC and APACHE II score.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis including 301 AP patients, MRI revealed that 24.9% exhibited at least one peripancreatic vascular abnormality related to AP, and the incidence of peripancreatic vascular involvement was notably more pronounced in necrotizing pancreatitis compared to edematous pancreatitis[ 76 ]. The common manifestations of early AP on MRI were splenic vein phlebitis and splenic artery involvement/arteritis, and 6.3% of the patients had splenic artery arteritis complicated with hemorrhage in the early phase of AP[ 76 ].…”
Section: Imaging Technologymentioning
confidence: 99%